Polyhedral single crystal alumina / aluminum nitride / epoxy resin thermal conductive composite material and preparation method thereof

By using polyhedral single crystal alumina and aluminum nitride fillers in epoxy resin composites to build continuous thermal conductivity channels, the problem of poor thermal conductivity of epoxy resin composites is solved, and efficient heat transfer and material performance improvement is achieved.

CN113861620BActive Publication Date: 2025-01-14CNBM RESEARCH INSTITUTE FOR ADVANCED GLASS MATERIALS GROUP CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202111124948.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-09-25
Publication Date
2025-01-14
Estimated Expiration
2041-09-25

AI Technical Summary

Technical Problem

The poor thermal conductivity of epoxy resin composites leads to chip heating problems and aging of insulating media, reducing the reliability and life of the chip.

Method used

Polyhedral single crystal alumina and aluminum nitride are used as fillers, and the traditional point-point contact method is replaced by mutual overlap between surface-surface and line-line to build an efficient continuous and wide heat conduction channel, and through modification and low-speed mixing , vacuum defoaming and other steps to prepare thermal composite materials.

Benefits of technology

The thermal conductivity of epoxy resin composite materials is significantly improved, the interface thermal resistance is reduced, the rapid transmission of heat is achieved, the thermal conductivity is increased to 3.0~6.0 W/mK, and the dielectric constant and mechanical strength are also improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 210925164319
    Figure 210925164319
  • Figure 210925164323
    Figure 210925164323
  • Figure 210925164339
    Figure 210925164339
Patent Text Reader

Abstract

The present invention relates to a polyhedral single crystal alumina / aluminum nitride / epoxy resin thermal conductive composite material and a preparation method thereof, characterized in that: (1) 20 to 75 parts of polyhedral single crystal alumina powder with D50=18 to 22um, 5 to 30 parts of aluminum nitride powder with D50=2 to 4um, 2 to 8 parts of polyhedral single crystal alumina with D50=0.3 to 0.5um, and 10 to 50 parts of E51 epoxy resin are taken for standby; (2) the polyhedral single crystal alumina and aluminum nitride powder are subjected to dry modification; (3) the modified powder, curing agent and accelerator are added to a star mill for mixing; then added to a vacuum degassing machine for degassing; and then subjected to curing treatment. Advantages of the present invention: the use of a ternary particle size close stacking system not only realizes close stacking, but also constructs an efficient, continuous and wide heat conduction channel, reducing the interface thermal resistance; the thermal conductivity of the epoxy resin composite material obtained is 3.0 to 6.0 W / mK, and has good insulation and mechanical properties.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparation of thermally conductive insulating composite materials, and in particular relates to a polyhedral single crystal aluminum oxide / aluminum nitride / epoxy resin thermally conductive composite material and a preparation method thereof. Background Art

[0002] With the rapid development of the electronic power industry, electrical and electronic equipment is also gradually developing towards high frequency, high speed, high power density and light weight, especially 5G communication chips. 5G high-frequency communication millimeter waves have ultra-high-speed transmission, ultra-low latency and ultra-large connection performance, but they will also increase chip power consumption and heat generation, thereby accelerating the aging of the insulating medium and reducing the reliability and life of the chip. Therefore, chip thermal management has become an important issue. As a 5G chip substrate and packaging material, it is required to improve the thermal conductivity of the insulating medium and reduce the dielectric constant and dielectric loss to achieve the purpose of accelerating chip heat dissipation and signal transmission speed.

[0003] Epoxy resin has excellent insulation properties, chemical resistance and bonding strength, and is widely used in electronic insulation materials. However, pure epoxy resin has poor thermal conductivity (thermal conductivity coefficient 0.18~0.25W / mK). By compounding and filling inorganic thermal conductive fillers with different structures, morphologies and particle sizes to effectively construct thermal conductive paths, the thermal conductivity of epoxy resin composite materials can be improved. Currently, the high thermal conductivity inorganic fillers filled are mainly spherical Al2O3 (30.0W / mK), AlN (319W / mK) and flaky / spherical h-BN (300-2000). Among them, h-BN has a higher unit price. Considering the thermal conductivity, system viscosity, filling amount and economic cost, spherical Al2O3 is the mainstream thermal conductive filler in the current domestic and foreign markets. It is generally used as an important skeleton inorganic thermal conductive filler. The thermal conductivity of its epoxy resin thermal conductive composite material is generally 1.0~3.0W / mK. As we all know, spherical alumina constructs a point-to-point contact heat conduction path, which is not conducive to constructing a continuous and wide heat conduction path, resulting in poor thermal conductivity of the composite material. Summary of the invention

[0004] The purpose of the present invention is to solve the problem of poor thermal conductivity of epoxy resin composite materials, and to provide a polyhedral single crystal alumina / aluminum nitride / epoxy resin thermal conductive composite material and a preparation method thereof; the composite material of the present invention omits the high-cost boron nitride, and instead uses low-cost alumina and aluminum nitride as fillers, thereby greatly reducing the production cost of the composite material; secondly, the present invention adopts a ternary particle size system, and replaces the point-to-point contact method between traditional spherical aluminas through the face-to-face and line-to-line overlap between polyhedral aluminas and polyhedral aluminas, and between polyhedral aluminas and aluminum nitride, so that not only can close stacking be achieved in the epoxy resin matrix, but also the interface thermal resistance can be effectively reduced while constructing an efficient, continuous and wide heat conduction channel, thereby ultimately enabling heat to be effectively and quickly transmitted.

[0005] In order to achieve the above object, the technical solution adopted by the present invention is as follows:

[0006] A polyhedral single crystal aluminum oxide / aluminum nitride / epoxy resin thermal conductive composite material, characterized by being made of the following raw materials in percentage by weight:

[0007]

[0008] A method for preparing a polyhedral single crystal aluminum oxide / aluminum nitride / epoxy resin thermal conductive composite material, characterized by comprising the following steps:

[0009] (1) Weigh the raw materials according to the above ratio and set aside;

[0010] (2) Modification: Dry modification of polyhedral single crystal aluminum oxide and aluminum nitride powders;

[0011] (3) Low-speed mixing: the epoxy resin, polyhedral single crystal alumina and aluminum nitride powder, curing agent and accelerator are put into a star mill for low-speed mixing (rotation speed: 100-300 rpm) to obtain epoxy resin composite slurry A;

[0012] (4) Vacuum degassing: adding the epoxy resin composite slurry in the above (3) into a vacuum degassing machine (rotation speed: 1000-3000 rpm) for degassing to obtain epoxy resin composite material slurry B;

[0013] (5) Casting-curing: The epoxy resin composite slurry in the above (4) is added to the stainless steel mold for curing treatment to obtain a polyhedral single crystal alumina / aluminum nitride / epoxy resin thermal conductive composite material.

[0014] Furthermore, in the step (1), the coupling agent used for modifying the polyhedral single crystal aluminum oxide and aluminum nitride is A-187 (a product of Momentive Corporation, USA), and the amount added is 1-6% of the weight of the powder.

[0015] Furthermore, in step (2), the curing agent is any one or more of methyltetrahydrophthalic anhydride (MeTHPA), methylhexahydrophthalic anhydride (MeHHPA), methylnadic anhydride (MNA), and dicyandiamide (DICY).

[0016] Furthermore, in step (2), the curing accelerator is any one or more of 2-ethyl-4-methylimidazole, 2-methylimidazole, DMP-10, DMP-20, and DMP-30.

[0017] Furthermore, a planetary ball mill is used for low-speed mixing, the grinding medium is 0.3-2 mm zirconium oxide beads, the mixing time is 60-240 min, and the rotation speed is 100-300 rpm.

[0018] Furthermore, a high-speed vacuum degassing machine is used for degassing, wherein 0.3-0.6 mm zirconium oxide beads are added, the mixing time is 30-120 min, and the rotation speed is 1000-3000 rpm.

[0019] Compared with the prior art, the present invention has the following advantages:

[0020] 1. In order to construct a broad and effective heat conduction path, the present invention adopts a ternary particle size system of large, medium and small inorganic fillers for hybrid overlapping, and obtains a lower viscosity system, the best thermal conductivity and the smallest interface thermal resistance under the premise of achieving close stacking (maximum filling);

[0021] 2 The present invention selects large-size polyhedral single-crystal alumina as the skeleton filler, which has the advantages of line-to-line and surface-to-surface contact compared with the point-to-point contact between traditional spherical alumina fillers; the heat conduction path constructed by large-size polyhedral single-crystal alumina is more continuous and wider than that of traditional alumina fillers, and can dissipate a large amount of heat in a timely and effective manner;

[0022] 3. The present invention adds small-size polyhedral alumina as a caulking agent to construct a number of heat conduction paths similar to country roads, which can promptly and effectively diffuse heat to surrounding heat conduction paths similar to provincial roads and corridors;

[0023] 4. The thermal conductive filler selected in the present invention has good dielectric constant and mechanical strength, and greatly improves the thermal conductivity of the epoxy resin composite material while ensuring good insulation and mechanical properties; the epoxy resin composite material prepared in the present invention has a thermal conductivity of 3.0-6.0 W / mK, a dielectric constant of 5.0-8.0 (1.0 MHZ), and a storage modulus of 7.0-17.0 GPa (100°C) (see Appendix 1 for specific thermal conductivity);

[0024] 5. The preparation method of the present invention is simple, easy to industrialize and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The SEM and particle size distribution diagram of large-sized polyhedral alumina;

[0026] Figure 2 This is the SEM-EDS image of aluminum nitride;

[0027] Figure 3 The SEM and XRD images of small-sized polyhedral alumina;

[0028] Figure 4 This is the SEM image of the cross section of the epoxy resin composite material.

[0029] Specific implementation cases:

[0030] A method for preparing a polyhedral single crystal aluminum oxide / aluminum nitride / epoxy resin thermally conductive composite material, the specific implementation steps are as follows:

[0031] Thermal conductivity of epoxy resin composite materials in the following examples λ = ρ × C p ×α, Where α is the thermal diffusion coefficient ,C p is the specific heat capacity, ρ is the density of the composite material, thermal diffusion coefficient ( α ) was measured using an LFA-457 laser thermal conductivity meter. The test sample was a cylinder with a diameter of 12.8 mm and a thickness of 2 mm.

[0032] Example 1

[0033] (1) According to the following components and weight ratios: 45 parts of polyhedral single crystal alumina (D50 = 20um), 12 parts of aluminum nitride (D50 = 2.5um), and 3 parts of polyhedral single crystal alumina (D50 = 0.30um);

[0034] (2) Modification: Add 1% A-187 by weight of the powder to the above-mentioned polyhedral single crystal alumina (D50 = 20 um), add 5% A-187 by weight of the powder to the polyhedral single crystal alumina (D50 = 0.30 um), and add 3% A-187 by weight of the powder to aluminum nitride (D50 = 2.5 um), and modify at 120°C for 45 minutes to obtain a modified inorganic thermal conductive powder;

[0035] (3) Low-speed mixing: Take 40 parts of E51 epoxy resin, 45 parts of modified polyhedral alumina (D50=20um), 12 parts of aluminum nitride (D50=2.5um), 3 parts of polyhedral alumina (D50=0.30um), add 10% of the weight of the powder as curing agent MeTHPA, 2‰ of accelerator MP-30, put into a planetary ball mill for low-speed mixing, the grinding medium is 1mm zirconium oxide beads, the mixing time is 180min, the rotation speed is 150rpm, and epoxy resin composite slurry A is obtained;

[0036] (4) High-speed vacuum degassing: The epoxy resin composite slurry A in the above (3) is added into a high-speed vacuum degassing machine for degassing, and 0.3 mm zirconium oxide beads are added. The degassing time is 45 min and the rotation speed is 2000 rpm to obtain epoxy resin composite material slurry B;

[0037] (5) Casting-curing: The epoxy resin composite slurry B in the above (4) was added to the stainless steel mold for curing treatment, pre-cured at 170°C for 1 h, and post-cured at 150°C for 7 h to obtain a polyhedral single crystal alumina / aluminum nitride / epoxy resin thermal conductive composite material.

[0038] Example 2

[0039] (1) According to the following components and weight ratios: 61 parts of polyhedral single crystal alumina (D50 = 22um), 15 parts of aluminum nitride (D50 = 3.5um), and 4 parts of polyhedral single crystal alumina (D50 = 0.35um);

[0040] (2) Modification: Add 1% A-187 by weight of the powder to the above-mentioned polyhedral single crystal alumina (D50=22um), add 5% A-187 by weight of the powder to the polyhedral single crystal alumina (D50=0.35um), and add 3% A-187 by weight of the powder to aluminum nitride (D50=3.5um), and modify at 120°C for 45 minutes to obtain a modified inorganic thermal conductive powder;

[0041] (3) Low-speed mixing: Take 10 parts of E51 epoxy resin, 61 parts of modified polyhedral alumina (D50=22um), 15 parts of aluminum nitride (D50=3.5um), 4 parts of polyhedral alumina (D50=0.35um), add 8% of the powder weight of curing agent MeTHHA, 2.5‰ of accelerator MP-10, put into a planetary ball mill for low-speed mixing, the grinding medium is 2.0mm zirconium oxide beads, the mixing time is 120min, the rotation speed is 130rpm, and epoxy resin composite slurry A is obtained;

[0042] (4) High-speed vacuum degassing: The epoxy resin composite slurry A in the above (3) was added into a high-speed vacuum degassing machine for degassing for 30 min, 0.6 mm zirconia beads were added, the degassing time was 60 min, and the speed was 1500 rpm to obtain epoxy resin composite material slurry B;

[0043] (5) Casting-curing: The epoxy resin composite slurry B in the above (4) was added to the stainless steel mold for curing treatment, pre-cured at 170°C for 1 h, and post-cured at 150°C for 7 h to obtain a polyhedral single crystal alumina / aluminum nitride / epoxy resin thermal conductive composite material.

[0044] Example 3

[0045] (1) According to the following components and weight ratios: 65 parts of polyhedral single crystal alumina (D50 = 18um), 16 parts of aluminum nitride (D50 = 4.5um), and 4 parts of polyhedral single crystal alumina (D50 = 0.25um);

[0046] (2) Modification: Add 1.5% A-187 by weight of the powder to the above-mentioned polyhedral single crystal alumina (D50=18um), add 4.5% A-187 by weight of the powder to the polyhedral single crystal alumina (D50=0.25um), and add 2.5% A-187 by weight of the powder to the aluminum nitride (D50=4.5um), and modify at 120°C for 45 minutes to obtain a modified inorganic thermal conductive powder;

[0047] (3) Low-speed mixing: Take 10 parts of E51 epoxy resin, 65 parts of modified polyhedral alumina (D50=18um), 16 parts of aluminum nitride (D50=4.5um), 4 parts of polyhedral alumina (D50=0.25um), add 8% of the powder weight of curing agent DIDY, 4‰ of accelerator 2-ethyl-4-methylimidazole, and 30% of polar solvent DMF, put into a planetary ball mill for low-speed mixing, the grinding medium is 0.6mm zirconium oxide beads, the mixing time is 170min, and the rotation speed is 200rpm to obtain epoxy resin composite slurry A;

[0048] (4) High-speed vacuum degassing: The epoxy resin composite slurry A in the above (3) was added into a high-speed vacuum degassing machine for degassing for 60 min, 0.3 mm zirconia beads were added, the degassing time was 60 min, and the speed was 2500 rpm to obtain epoxy resin composite material slurry B;

[0049] (5) Casting-curing: The epoxy resin composite slurry in the above (4) is added to the stainless steel mold for curing treatment, pre-curing at 170°C for 1 hour, and post-curing at 150°C for 7 hours to obtain a polyhedral single crystal alumina / aluminum nitride / epoxy resin thermal conductive composite material.

[0050]

Claims

1. A method for preparing a polyhedral single crystal aluminum oxide / aluminum nitride / epoxy resin thermal conductive composite material, characterized in that: The following steps are involved: (1) According to the following components and weight ratios: 65 parts of polyhedral single crystal aluminum oxide with D50 = 18um, 16 parts of aluminum nitride with D50 = 4.5um, and 4 parts of polyhedral single crystal aluminum oxide with D50 = 0.25um; (2) Modification: Add 1.5% A-187 by weight of powder to the above-mentioned polyhedral single crystal alumina with D50 = 18 um, add 4.5% A-187 by weight of powder to the polyhedral single crystal alumina with D50 = 0.25 um, and add 2.5% A-187 by weight of powder to the aluminum nitride with D50 = 4.5 um, and modify at 120°C for 45 minutes to obtain a modified inorganic thermal conductive powder; (3) Low-speed mixing: Take 10 parts of E51 epoxy resin, 65 parts of modified polyhedral alumina with D50 = 18um, 16 parts of aluminum nitride with D50 = 4.5um, 4 parts of polyhedral alumina with D50 = 0.25um, add 8% of the powder weight of curing agent DICY, 4‰ of accelerator 2-ethyl-4-methylimidazole, and 30% of polar solvent DMF, put into a planetary ball mill for low-speed mixing, the grinding medium is 0.6mm zirconium oxide beads, the mixing time is 170min, and the rotation speed is 200rpm to obtain epoxy resin composite slurry A; (4) High-speed vacuum degassing: The epoxy resin composite slurry A in the above (3) was added into a high-speed vacuum degassing machine for degassing for 60 min, 0.3 mm zirconia beads were added, the degassing time was 60 min, and the speed was 2500 rpm to obtain epoxy resin composite material slurry B; (5) Casting-curing: adding the epoxy resin composite slurry in the above (4) into a stainless steel mold for curing treatment, pre-curing at 170° C. for 1 h, and post-curing at 150° C. for 7 h to obtain a polyhedral single crystal alumina / aluminum nitride / epoxy resin thermal conductive composite material; The thermal conductivity of the thermally conductive composite material is 5.46 W / mK, the dielectric constant is 7.26 at 1.0 MHz, and the storage modulus is 16.72 GPa at 100 °C.

Citation Information

Patent Citations

  • Resin composition sheet, resin composition sheet with metal foil, metal base wiring board material, metal base wiring board and electronic member

    JP2013014671A